Research on spontaneous combustion law and precise prevention and control technology of extra thick residual coal in multi layered staggered mining - Yanhui XU; Xiaojiao CHENG; Hu WEN; Xiaowei ZHAI; Shixing FAN; Yongfei JIN; Yin LIU; Zhijin YU (Meitan kexue jishu)
The average thickness of VI coal seam in Barapukuria mine in Bangladesh is 36 m. The damage reduction mining mode with layered staggered arrangement is adopted. The geological conditions are complex, the original ground temperature is high, and the geological disasters such as spontaneous combustion fire, water damage, heat damage and rock burst are serious. In view of the environmental conditions conducive to coal spontaneous combustion, such as large amount of residual coal in goaf, many three-dimensional air leakage and oxygen supply channels, water loss of residual coal and high ground temperature in multi-layer staggered mining of Mengba Mine, firstly, through the theoretical superposition of “three zones” observation of coal spontaneous combustion in goaf, air leakage channel analysis, tension fracture zone and fault, the range and risk level of spontaneous combustion danger area in multi-layer staggered mining are divided, and the minimum safe advance speed of working face is determined. Secondly, through the programmed temperature rise experiment of different water-bearing coal samples and Graham coefficient, the coal spontaneous combustion marker gas, characteristic temperature threshold, early warning index and threshold are obtained. Combined with the distribution characteristics of goaf, goaf and roadway dangerous area, the monitoring and early warning method of “space-time-classification-adaptation” for spontaneous combustion dangerous area in multi-layer mining is proposed. According to the characteristics of layered staggered mining in Mengba Mine and many years of field practice, the precise prevention of “three-dimensional plugging, segmented isolation, regional nitrogen injection” in dangerous areas and the emergency control technology of “traceability control leakage, reduction dilution, directional drainage” of catastrophic gas are formed. The field application results show that the implementation of this technology ensures the safe unsealing of the 1110 working face of the first layer, and liberates 800,000 tons of stagnant coal. In addition, the oxidation process of residual coal in the goaf during the normal mining process of each stratified working face is effectively controlled. The CO in the goaf on the air inlet side is 0, and the CO in the goaf on the air return side is rapidly reduced to 0 in a short time, which successfully guarantees the safe mining of Mengba Mine for more than ten years.